Five new compounds from Zingiberis Rhizoma Recens and their anti-apoptotic activity. Issue 1 (2nd January 2023) - Zhang, Xiao-Juan; Song, Zhi-Min; Yuan, Pei-Pei; Wang, Yan-Zhi; Li, Man-Qian; Liu, Yu-Fei; Hu, Xue-Yu; Feng, Wei-Sheng
Abstract: Five new compounds, named gingerol A (1a and 1b ), gingerol B (2 ), diphenylheptane glycoside A (3 ) and diphenylheptane glycoside B (4 ), were isolated from the acetone extract of Zingiberis Rhizoma Recens. The structures of new compounds were elucidated on the basis of spectroscopic methods including UV, IR, 1D NMR, 2D NMR and HR-ESI-MS. Compounds 2 –4 could significantly decrease the apoptosis rate and increase the survival rate of human normal lung epithelial cells (BEAS-2B) at the concentration of 10 μM. Graphical Abstract: UF0001